Browning kinetics of egg white during high-temperature process - Tangduangdee, Chairath; Asavasanti, Suvaluk; Taichan, Kanruethai (Bulletin of Applied Sciences, 2023)
Egg white product is commonly produced by pasteurization to avoid brown color development and needs to be kept in a refrigerator. To explore the opportunity of producing shelf-stable egg white products, this research aimed to develop the browning kinetic model of egg white undergoing a high-temperature treatment and to minimize the browning reaction by desugaring with glucose oxidase. Egg white (8 mL) was filled in sample holders equipped with a thermocouple. The sample holders were preheated in a water bath at 70°C for 30 minutes to solidify the sample and then heated in an oil bath at 100, 110, and 130°C for 30 minutes. The color of the sample surface was measured using a spectrophotometer. The yellowness index (YI) was calculated to identify the degree of brown color development. It was found that the L* value of egg white declined, while a* and b* values increased with increasing heating time. The first-order kinetic model was applicable for predicting the change of YI-ratio (R2 = 092-0.95, RMSE = 0.11-029). In addition, the samples pre-treated with glucose oxidase of 30 units/mL-egg white and 30°C-incubation for 6.5 hours had a significant reduction of the YI-ratio from 5.9 to 2.6. This research indicates the potential for egg-white production at a high temperature with lighter color by adding glucose oxidase.